2021
DOI: 10.1142/s0218488521500173
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Data Envelopment Analysis with Ordinal and Interval Data

Abstract: In this paper, we reformulate the conventional DEA models as an imprecise DEA problem and propose a novel method for evaluating the DMUs when the inputs and outputs are fuzzy and/or ordinal or vary in intervals. For this purpose, we convert all data into interval data. In order to convert each fuzzy number into interval data, we use the nearest weighted interval approximation of fuzzy numbers by applying the weighting function, and we convert each ordinal data into interval one. In this manner, we could conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…When collecting self-reported data on behaviour, the main focus is on their final presentation, since, in many cases, respondents are not able to clearly express their judgments, and it is assumed that all final values derived from such data are uncertain [21]. Recently, in an uncertain DEA framework, imprecise DEA approaches [22], fuzzy DEA methods [23], and robust DEA methods [24] have been used. In [25,26], it was shown that both imprecise DEA and fuzzy DEA models can give robust composite index scores, which implies the effectiveness and reliability of these two approaches for modelling qualitative data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…When collecting self-reported data on behaviour, the main focus is on their final presentation, since, in many cases, respondents are not able to clearly express their judgments, and it is assumed that all final values derived from such data are uncertain [21]. Recently, in an uncertain DEA framework, imprecise DEA approaches [22], fuzzy DEA methods [23], and robust DEA methods [24] have been used. In [25,26], it was shown that both imprecise DEA and fuzzy DEA models can give robust composite index scores, which implies the effectiveness and reliability of these two approaches for modelling qualitative data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [25,26], it was shown that both imprecise DEA and fuzzy DEA models can give robust composite index scores, which implies the effectiveness and reliability of these two approaches for modelling qualitative data. Furthermore, in [23], it is illustrated that each fuzzy number can be converted into an interval number, thus reducing the issue of the DMUs' efficiency assessment to an imprecise DEA problem. In addition to the above, rough set theory, probability theory, Shannon's entropy, and grey theory have been put forward to deal with imprecise and ambiguous data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In data mining, transactions may be event related data in real world and are associated with intervals in both continuous and discrete domains such as intervals of distance, time, blood pressure, etc [2] [3]. An interval has start and end values associated with it [4] [5][6] [7] [8]. Interval data mining is a data mining approach that extracts hidden information, patterns, and association rules [27] from interval data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the support of any interval properly containing it will be less than the support of it. Let us consider a data set with two intervals I1= [4,7] andI2= [5,8] as shown in Figure 1. The overlapping (intersection) of these two intervals is the interval I3= [5,7].…”
Section: Introductionmentioning
confidence: 99%